Design of Multi-function Power Factor Instrument with STM32 - Qi, Wenjuan; Gao, Jixuan; Wang, Zhongxian (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: A multifunctional power factor device based on the FFT algorithm has been designed. The digital panel can display power factor, voltage, current, frequency, phase angle, active power and reactive power. Objective: To solve the influence of the harmonic interference and the aperiodic component on the accuracy of power factor measurement. Methods: In this paper, by combining a fixed-point 256-point FFT algorithm and taking STM32 as the core microcontroller, the hardware circuit and the software program are designed respectively. The hardware circuit is tested and analyzed in practice. Among them, the hardware circuit mainly includes the main circuit design, STM32 control circuit design, EMI and second-order RC filter circuit design, sampling circuit design, and signal conditioning circuit design. The software program mainly includes the main program, AD conversion subroutine, voltage and current acquisition subroutine, LCD display subroutine and twirl factor array. FFT algorithm is achieved by the table look-up method. Results: Finally, the hardware circuit is built and the software program is debugged to test the designed device. The experimental results show that the designed power factor instrument meets the task requirements under the different types of loads. Conclusion: After processing and analyzing the measurement results, it can be concluded that: under the pure resistive load, the maximal relative error of electrical parameters is 4.49%; and under the resistive inductive load, the maximal relative error of electrical parameters is 2.86%. Both results meet the design requirements.
Keywords: Power factor device